The Role of Audit Quality as Moderating Factors Influencing the Timeliness of Financial Reporting - Yogi Ananditya Nagari; Muhammad Nuryatno (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the role of Audit Quality in moderating the effect of Profitability, Firm Size, Public Ownership, and Audit Opinion on Timeliness of Financial Reporting, with Leverage as a control variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 to 2020. This study uses purposive sampling for 5 years of observation. The data were analyzed by descriptive statistical test, hypothesis testing by logistic regression analysis, F statistical analysis and t statistical analysis. The results showed that Profitability has a positive effect on the Timeliness of Financial Reporting. Meanwhile, Firm Size, Public Ownership and Audit Opinion have no effect on Timeliness of Financial Reporting. Leverage as a control variable cannot control the effect of the independent variable on the dependent variable. Audit Quality as a moderating variable cannot moderate the influence of Profitability, Firm Size, Public Ownership and Audit Opinion on Timeliness of Financial Reporting.